2009
DOI: 10.1017/s0007114509993060
|View full text |Cite
|
Sign up to set email alerts
|

Insulin release, peripheral insulin resistance and muscle function in protein malnutrition: a role of tricarboxylic acid cycle anaplerosis

Abstract: Pancreatic beta-cells and skeletal muscle act in a synergic way in the control of systemic glucose homeostasis. Several pyruvate-dependent and -independent shuttles enhance tricarboxylic acid cycle intermediate (TACI) anaplerosis and increase beta-cell ATP:ADP ratio, triggering insulin exocytotic mechanisms. In addition, mitochondrial TACI cataplerosis gives rise to the so-called metabolic coupling factors, which are also related to insulin release. Peripheral insulin resistance seems to be related to skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 163 publications
0
7
0
2
Order By: Relevance
“…Most investigations found a reduced number or attenuated in vivo activity of muscle mitochondria in insulin resistant subjects [39]; [66]; [67] [36][38], but others have reported that the function of isolated muscle mitochondria is normal in T2DM [68]; [69]. This raises the possibility that factors limiting mitochondrial activity in diabetics in situ are lost in studies in isolated organelles.…”
Section: Discussionmentioning
confidence: 99%
“…Most investigations found a reduced number or attenuated in vivo activity of muscle mitochondria in insulin resistant subjects [39]; [66]; [67] [36][38], but others have reported that the function of isolated muscle mitochondria is normal in T2DM [68]; [69]. This raises the possibility that factors limiting mitochondrial activity in diabetics in situ are lost in studies in isolated organelles.…”
Section: Discussionmentioning
confidence: 99%
“…; Zoppi et al . ); (ii) meeting muscle ATP needs through FAO can take place without full combustion of the fat in the TCA cycle: for any given ATP requirement, one may generate chain‐shortened fatty acid metabolites through β‐oxidation that do not enter the TCA cycle at all, but simply accumulate or are exported from mitochondria; and (iii) while measuring muscle fibre metabolism ex vivo is an improvement over isolated mitochondria, bioenergetics profiles comparing insulin‐resistant and insulin‐sensitive preparations will still be strongly influenced by the ATP turnover requirements of the cells, which may differ. With these concepts in mind, we set out to determine whether incomplete LCFA combustion (viz.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the assertion that mitochondrial dysfunction underlies diabetes phenotypes has been questioned, because isolated mitochondria from insulin-resistant or T2DM individuals can display normal bioenergetics, and the muscle is calculated to have oxidative capacity that far exceeds what is required for maximal ATP generation (see Holloszy, 2009). Reconciling these various perspectives must take into account several key principles, as follows: (i) studies using isolated mitochondria are provided with fuel and anaplerotic TCA substrates artificially, potentially masking intrinsic perturbations of TCA activity that occur in situ due to 'anaplerotic/cataplerotic stress' (Adams et al 2009;Fiehn et al 2010;Zoppi et al 2010); (ii) meeting muscle ATP needs through FAO can take place without full combustion of the fat in the TCA cycle: for any given ATP requirement, one may generate chain-shortened fatty acid metabolites through β-oxidation that do not enter the TCA cycle at all, but simply accumulate or are exported from mitochondria; and (iii) while measuring muscle fibre metabolism ex vivo is an improvement over isolated mitochondria, bioenergetics profiles comparing insulin-resistant and insulin-sensitive preparations will still be strongly influenced by the ATP turnover requirements of the cells, which may differ. With these concepts in mind, we set out to determine whether incomplete LCFA combustion (viz.…”
Section: Discussionmentioning
confidence: 99%
“…The insulin secretion values reported by our results, showed near 50% reduction in LP GIIS, which is in agreement with other reports (Ferreira et al, , ; Filiputti et al, ). In a recent review, we presented molecular and metabolic alterations induced by protein malnutrition such as: Reduced insulin mRNA, PDX‐1 and protein kinases A and C expression, calcium influx, glucose oxidation, and anaplerotic capacity, which, taken together, may partially explain the observed reduction in low‐protein‐fed state GIIS (Zoppi et al, ). However, the redox control of GIIS under protein undernourishment status remained unclear.…”
Section: Discussionmentioning
confidence: 99%